Digitalization of public administration: expert reflection on problems and challenges - E. I. Boev; V. V. Zotov; L. A. Vasilenko (Цифровая социология)
In the article, the authors identified a set of conditions and factors that both hinder and facilitate the transformation of public administration as a public-state system for coordinating and realizing the interests of representatives of stakeholders through the use of the potential of digital and information and telecommunication technologies. In the course of the study, the following tasks were solved: the role of digitalization for the public administration system was assessed, the problems of this process were identified, the possibilities of electronic online platforms in the organization of social networking in the “governance – society” dyad were evaluated. The article presents the results of a focused group semi-formalized online interview in the format of video conferencing on the Zoom platform, conducted in December 2021 among 20 experts. The experts were representatives of public authorities at the federal, regional and local levels, state corporations, civil society structures, business structures, the scientific community, as well as the Russian Regional Management Center. Based on the analysis of the results of the expert survey, the authors conclude that the digitalization of the activities of the authorities gives a good increase not only in improving the quality of service provision to the country’s population, but also in improving the feedback mechanism, increasing the involvement of the population in the process of solving socially significant issues. This gives hope that the resolution of problems associated with the introduction of digital technologies into the work of government bodies with the population will contribute to the transition from informing and servicing citizens to interactive communication with them.